Integrating pharmacists into primary care teams: barriers and facilitators. (27th November 2013) - Jorgenson, Derek; Laubscher, Tessa; Lyons, Barry; Palmer, Rebecca
Abstract Objectives This study evaluated the barriers and facilitators that were experienced as pharmacists were integrated into 23 existing primary care teams located in urban and rural communities in Saskatchewan, Canada. Methods Qualitative design using data from one‐on‐one telephone interviews with pharmacists, physicians and nurse practitioners from the 23 teams that integrated a new pharmacist role. Four researchers from varied backgrounds used thematic analysis of the interview transcripts to determine key themes. The research team met on multiple occasions to agree on the key themes and received written feedback from an external auditor and two of the original interviewees. Key findings Seven key themes emerged describing the barriers and facilitators that the teams experienced during the pharmacist integration: (1) relationships, trust and respect; (2) pharmacist role definition; (3) orientation and support; (4) pharmacist personality and professional experience; (5) pharmacist presence and visibility; (6) resources and funding; and (7) value of the pharmacist role. Teams from urban and rural communities experienced some of these challenges in unique ways. Conclusions Primary care teams that integrated a pharmacist experienced several common barriers and facilitators. The negative impact of these barriers can be mitigated with effective planning and support that is individualized for the type of community where the team is located.